The associations between adolescents' sports club participation and dietary habits - Heikkilä Laura; Korpelainen Raija; Aira Tuula; Alanko Lauri; Heinonen Olli J.; Kokko Sami; Kujala Urho; Parkkari Jari; Savonen Kai; Valtonen Maarit; Vasankari Tommi; Villberg Jari; et al. (WILEY, 2022)
For adolescent athletes, data on nutrition behaviors are limited. The present study aimed to evaluate the dietary habits of adolescent sports club participants (SPs) compared with those of non-participants (NPs). The cross-sectional study of 1917 adolescents aged 14-16 was based on data from the Finnish Health Promoting Sports Club (FHPSC) study. The health behavior surveys were conducted among SPs (n = 1093) and NPs (n = 824). Logistic regression was used to test statistical significance of the differences in dietary habits between SPs and NPs. SPs were more likely than NPs to eat breakfast on weekends [89% vs 79%, odds ratio (OR) 1.46, 95% confidence interval (CI) 1.07-2.01] and to report daily consumption of vegetables (46% vs 32%, OR 1.33, 95% CI 1.04-1.69) and fat-free or semi-skimmed milk (72% vs 55%, OR 1.33, 95% CI 1.04-1.68). Dietary habits regarded as unhealthy, such as sugared soft drink consumption, were similar between the groups. The aforementioned healthy dietary habits are more frequent in SPs than NPs, and unhealthy dietary habits are equally frequent in the groups. Both adolescent SPs' and NPs' dietary habits have deficiencies, like inadequate vegetable and fruit consumption. Sports clubs' opportunities for adolescents' healthy eating promotion should be examined.